Coping with stigma and discrimination: evidence from mental health service users in England. (2nd May 2017) - Isaksson, A.; Corker, E.; Cotney, J.; Hamilton, S.; Pinfold, V.; Rose, D.; Rüsch, N.; Henderson, C.; Thornicroft, G.; Evans-Lacko, S.
Abstract : Aims: Mental health stigma and discrimination are significant problems. Common coping orientations include: concealing mental health problems, challenging others and educating others. We describe the use of common stigma coping orientations and explain variations within a sample of English mental health service users. Methods: Cross-sectional survey data were collected as part of the Viewpoint survey of mental health service users' experiences of discrimination ( n = 3005). Linear regression analyses were carried out to identify factors associated with the three stigma coping orientations. Results: The most common coping orientation was to conceal mental health problems (73%), which was strongly associated with anticipated discrimination. Only 51% ever challenged others because of discriminating behaviour, this being related to experienced discrimination, but also to higher confidence to tackle stigma. Conclusions: Although stigma coping orientations vary by context, individuals often choose to conceal problems, which is associated with greater anticipated and experienced discrimination and less confidence to challenge stigma. The direction of this association requires further investigation.